Ratiometric fluorescent sensing of pyrophosphate with sp³-functionalized single-walled carbon nanotubes [data] - Settele, Simon; Schrage, C. Alexander; Jung, Sebastian Thomas; Michel, Elena; Li, Han; Flavel, Benjamin S.; Hashmi, A. Stephen K.; Kruss, Sebastian; Zaumseil, Jana (Universität, 2024)
Underlying data for all figures in the paper "Ratiometric fluorescent sensing of pyrophosphate with sp³-functionalized single-walled carbon nanotubes. Nat. Commun. 2024, 15, 706.
Finanziert durch: European Research Council (ERC): 817494
Gesehen am 02.04.2024
Keywords: Forschungsdaten; Datenbank